Domestic violence against the man: the structure of emotional experience - Alifanovienė, Daiva; Šapelytė, Odeta; Patkauskienė, Lina (Social Welfare: Interdisciplinary Approach, 2013)
The article presents problems of domestic violence in the context of women violence against the man. Domestic violence became one of the dominating and most controversially valued conceptual areas in the scientifc discourse. The qualitative study aimed to disclose emotional experiences of the man who has experienced violence in the closest environment. The study disclosed broad and exhaustive spectrum of emotional experiences of the man who has experienced woman’s violence. Applying content analysis method, fve categories describing the structure of the man’s emotional experiences and refecting emotional experiences to be related to the very self, wife, stepmother, environment and mother-in-law were identifed.
Keywords: domestic violence; emotional experience; women violence against the man